Osteopontinspiegel im Plasma bei dilatativer und hypertrophischer Kardiomyopathie - Podzimkova, J; Palecek, T; Kuchynka, P; Marek, J; Danek, Barbara Anna; Jachymova, M; Kalousova, M; Zima, T; Linhart, A (Herz, 2019)
BACKGROUND: Osteopontin (OPN) is an extracellular matrix glycoprotein that plays a role in a variety of cellular activities associated with inflammatory and fibrotic responses. Increased OPN levels in myocardium and plasma have been demonstrated in patients with dilated cardiomyopathy (DCM). However, nothing is known about OPN levels in patients with hypertrophic cardiomyopathy (HCM). Therefore, the aim of our study was to compare plasma OPN levels in patients with these two most common cardiomyopathies. PATIENTS AND METHODS: We examined plasma OPN as well as creatinine, C‐reactive protein (CRP), brain-type natriuretic peptide (BNP), and troponin I levels in 64 patients with DCM, 43 patients with HCM, and 75 control subjects. Transthoracic echocardiography was also performed on all cardiomyopathy patients. RESULTS: Plasma OPN levels were significantly elevated in patients with DCM compared with HCM patients (95 ± 43 vs. 57 ± 21 ng/ml; p < 0.001) and control subjects (54 ± 19 ng/ml; p < 0.001); however, there was no difference between HCM patients and control subjects. New York Heart Association (NYHA) class III or IV disease was more frequently present in DCM patients than in HCM subjects (44 % vs. 2 %, p < 0.0001). In multivariate analysis, BNP and CRP levels together with NYHA class were found to be significant predictors of plasma OPN levels in DCM patients (p = 0.002, p = 0.029, and p < 0.001 for BNP, CRP, and NYHA, respectively). CONCLUSION: Plasma OPN levels were associated with overall heart failure severity rather than with specific cardiomyopathy subtype in patients suffering from DCM or HCM, respectively.
Keywords: ženské pohlaví; Female; Myocardium; Cardiomyopathy, Dilated; lidé středního věku; hypertrofická kardiomyopatie; lidé; Humans; myokard; Middle Aged; osteopontin; dilatační kardiomyopatie; Cardiomyopathy, Hypertrophic; Natriuretic Peptide, Brain; natriuretický peptid typu B; Male; mužské pohlaví; Osteopontin